2020
DOI: 10.1101/2020.07.28.20160630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotine-replacement therapy, as a surrogate of smoking, and the risk of hospitalization with Covid-19 and all-cause mortality: a nationwide, observational cohort study in France

Abstract: Introduction Several studies have reported an unexpectedly low prevalence of current smoking among hospitalized patients with Covid-19. However, these studies mostly compared observed to expected rates of smoking without direct comparison with individual controls. Objective To examine the association of nicotine-replacement therapy, as a surrogate of smoking, with hospitalization and all-cause mortality during the first wave of SARS-CoV-2 epidemic in France. Methods We conducted a nationwide matched expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Evidence from these studies is somehow contrasting, and the role of tobacco smoking, NRT, or vaping is still to be assessed [4][5][6][7][50][51][52][53][54][55][56][57]. In many cases, the presence of underreporting in recording smoking history at admission, especially to ICU during the COVID-19 outbreak, when the hospitals are overwhelmed, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from these studies is somehow contrasting, and the role of tobacco smoking, NRT, or vaping is still to be assessed [4][5][6][7][50][51][52][53][54][55][56][57]. In many cases, the presence of underreporting in recording smoking history at admission, especially to ICU during the COVID-19 outbreak, when the hospitals are overwhelmed, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, based on these findings, an acetylcholinesterase inhibitor 124, 125 and a nicotinic receptor agonist have been tested 126, 127 . However, recent studies have demonstrated that nicotine and smoking increase ACE2 receptor density 128, 129 , and that the potential beneficial effects of nicotine were restricted to a small group of individuals 130 . Our findings provide a warning that precautions should be taken when considering the therapeutic use of nicotinic agonists, since patients with severe/critical Covid-19 were found to release high amounts of ACh, in addition to showing increased levels of M3-receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cohort study on the National Health Data System (SNDS) that covers the entire French population, i.e. 67 million inhabitants, and which has been extensively used in France to conduct pharmaco-epidemiology studies [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ] including studies on the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%